Changes in barrier function of a model intestinal epithelium by intraepithelial lymphocytes require new protein synthesis by epithelial cells - KELLEHER, DERMOT P (BMJ, 1997)
BACKGROUND: Elements of the mucosal immune system may play an important part in regulating epithelial barrier function in the intestinal tract. Intraepithelial lymphocytes (IELs) represent a subtype of immunocyte which is strategically placed to regulate epithelial function at most mucosal sites. AIMS AND METHODS: An IEL derived cell line (SC1) was used to examine its effects on the model epithelium T84--a tumour derived cell line which retains the phenotype of colonic crypt cells. Transepithelial electrical resistance (TER) was used as a marker of epithelial integrity. RESULTS: Coculture of T84 cells with SC1 produced a significant fall in TER as did exposure of T84 monolayers to IEL derived supernatant. Recombinant interferon-gamma (rIFN gamma) also reduced TER in T84 monolayers. Cycloheximide prevented the effects of IEL supernatant and of rIFN gamma on TER. The fall in TER in response to rIFN gamma was attenuated by blocking antibodies, which did not alter the fall in resistance induced by IEL supernatant. Fractions of IEL supernatant, separated on the basis of size, evoked temporally distinct changes in TER. Ultrastructural studies support the hypothesis that the slow onset but severe fall in TER indicates catastrophic effects on the monolayer. The more rapid onset fall in TER was not associated with gross changes in monolayer morphology. Reduction of TER by IEL supernatant was not influenced by inhibitors of tyrosine phosphatase or of protein kinase C. Although herbimycin did reduce the rapid onset change in TER, the tyrosine kinase inhibitor genistein did not alter responses to IEL supernatant. CONCLUSIONS: Mucosal T cells may influence barrier function by a process involving new protein synthesis by epithelial cells. This model may have relevance in some inflammatory conditions of the gastrointestinal tract.
PUBLISHED
Keywords: Clinical Medicine